Diabetes Care in French Guiana: The Gap Between National Guidelines and Reality - Sudre, Christine; Duplan, Hélène; Bukasakakamba, John; Nacher, Mathieu; Peyre-Costa, Pascale; Sabbah, Nadia (Frontiers in Endocrinology, 2021)
Introduction: French Guiana is a multicultural overseas territory in the Amazon, where precariousness and difficulties in access to care are widespread. The prevalence of diabetes is double that of other French departments, and cardiovascular morbidity and mortality is high. The objective of the study was to analyze the biological, clinical and therapeutic follow-up of patients with diabetes mellitus using exhaustive data and to correlate it with national and European recommendations. Material and Methods: Using the national health insurance data, 9079 and 10075 patients with diabetes mellitus were analyzed in 2018 and 2019, respectively. We analyzed antidiabetic treatments, medical, dental, and podiatric consultations, examinations prescribed as part of the annual follow-up, and home nursing care. Results: There was a significant increase over one year in the number of patients (+10%) with diabetes, mainly women (60%), and 31% were under 54 years of age, with a disparity depending on the area of the territory, the most isolated having less access to screening. Less than 56% of patients had HbA1c measurements twice a year, less than 43% had an annual renal check-up, only 19% had an ophthalmic check-up at least every two years, less than 25% had an annual dental check-up, and less than 4% had an annual follow-up with the podiatrist. Conclusions: Substandard diabetes monitoring is a major problem likely to increase morbidity and mortality. Adapting health care to the specificities of the territory is crucial, notably by formalizing the delegation of care to advanced practice nurse and non-healthcare professionals in precarious or geographically isolated areas.